How do workers benefit from skill utilisation and how can these benefits be enhanced?. (November 2019) - Boxall, Peter; Huo, Meng-Long; Winterton, Jonathan
This article uses national-level data to examine the benefits for workers of better skill utilisation and the question of how opportunities to use skills in the workplace can be enhanced. Analysis of the New Zealand data in the 2005 and 2015 rounds of the International Social Survey Programme confirms that better skill utilisation is generally associated with a broad range of beneficial outcomes, including higher employee income, better opportunities for career advancement, higher job satisfaction, greater organisational commitment and lower turnover intentions. In addition, skill utilisation serves as a significant mediator between work autonomy and employee outcomes, particularly in the 2015 survey. As a general rule, better utilisation of employee skills will occur in organisational climates in which employee autonomy is encouraged.